Healthcare Access of Autistic Language Minorities: The Case of English Official Language Minorities in Quebec, Canada - Amantayev, Nariman; Rao, Sabrina; Nadig, Aparna (Minorités linguistiques et société, 2025)
Abstract English and French are both official languages in Canada. Whereas official language minorities (English speakers in Quebec, French speakers in the rest of Canada) face healthcare barriers and poor health outcomes, autistic individuals and their families also struggle with accessing healthcare. We examined healthcare access at the intersection of these groups: the autistic community, including English minority-language speakers from Quebec, French majority-language speakers from Quebec, and English majority-language speakers from elsewhere in Canada (n = 165). Linguistic minorities reported poorer access to publicly-funded services and lower satisfaction that their language needs were being met than did linguistic majorities. Foreign-born English speakers also experienced poorer access than their Canadian-born counterparts. These preliminary findings suggest that autistic language minorities face known barriers to accessing healthcare, potentially at a higher rate than that experienced by language minorities in general. Résumé L’anglais et le français sont les langues officielles du Canada. Les minorités de langue officielle (anglophones au Québec, francophones hors Québec) font face à des obstacles en matière de santé, tout comme les personnes autistes et leurs familles. Nous avons examiné l’accès aux services de santé à l’intersection de ces groupes : la communauté autiste, incluant des anglophones (minoritaires) et francophones (majoritaires) du Québec, ainsi que des anglophones (majoritaires) du reste du Canada (n = 165). Les minorités linguistiques déclarent un accès plus difficile aux services de santé publics et une moindre satisfaction quant à la prise en compte de leurs besoins linguistiques, comparativement aux majorités linguistiques. Les anglophones nés à l’étranger rapportent également un accès plus difficile que leurs pairs nés au Canada. Ces résultats préliminaires suggèrent que les minorités linguistiques autistes font face à des obstacles connus en matière d’accès aux soins, possiblement à un degré plus élevé.

Social service accessibility in Montreal’s English-speaking disability community: A needs-based assessment - Nash, Aubrey (McGill University, 2019)
Health and social service systems can be difficult to traverse, especially in the stressful situations that often necessitate accessing them. In Quebec, these difficulties are exacerbated for English speaking or limited French-proficient persons. This thesis employs a needs-based assessment to explore how linguistic-based access barriers to health and social services affect Montreal’s English-speaking Disability community, focusing on those with intellectual and/or developmental disabilities and their caregivers/advocates. It identifies the community’s needs and proposes three key issues that result in the needs being unmet by the social service system. Specifically, the issues are (i) inaccessible information for limited French-proficient persons, as many important documents are available in only French; (ii) the primary method for bolstering language congruency between service users and providers relies on the service seeker to acquire French, which is incompatible with the lived experiences of many members of the Disability community; (iii) limited options for English services across Montreal. This thesis indicates the protection of the French language under the Charter of the French Language (1977) impacts the ability of the Act Respecting Health Services and Social Services (1991) to protect the rights of English-speaking Quebeckers to receive services in English. Through a human rights model of Disability and citizenship lens, it suggests that language laws can be understood and implemented to protect the Quebecois identity while ensuring active inclusion of otherwise marginalized communities in health and social service systems

Workforce utilization of visible and linguistic minorities in Canadian nursing - Premji, Stephanie; Etowa, Josephine. B. (Journal of Nursing Management, 2012)
Background There is ample evidence of ethnic and linguistic segregation in the Canadian labour market. However, it is unknown if there is equitable representation of visible and linguistic minorities in nursing professions. Methods We cross-tabulated aggregate data from Statistics Canada’s 2006 Census. Analyses examined the distribution of visible and linguistic minorities, including visible minority sub-groups, among health managers, head nurses, registered nurses, licensed nurses and nurse aides for Canada and major cities as well as by gender. Results In Canada and its major cities, a pyramidal structure was found whereby visible and linguistic minorities, women in particular, were under-represented in managerial positions and over-represented in lower ranking positions. Blacks and Filipinos were generally well represented across nursing professions; however, other visible minority sub-groups lacked representation. Conclusions Diversity initiatives at all levels can play a role in promoting better access to and quality of care for minority populations through the increased cultural and linguistic competence of care providers and organizations.